The synthetic evaluation and analysis on technology of energy saving reform for existing public buildings in Shanghai Area. (October 2019) - Qu, Y; Liu, Y D; Hu, G X
Abstract: Nowadays, a large proportion of old buildings in Shanghai area cannot satisfy the energy efficiency standards, thus the reform of existing buildings still plays an important role in the process of achieving energy saving target. However, the systematic study and evaluation of corresponding technology and those completed demonstration projects is lacked, which has affected the clear and reasonable understanding of government and related owners about the effectiveness of those reform projects as well as the investment payback. In view of this, a synthetic study was carried out to investigate the characteristic of energy consumption for public buildings in Shanghai firstly. Then a deep analysis was conducted on the energy-saving reform technologies involved in those projects, including usage frequency, energy-saving ratio and economic performance. The results show that the demonstration projects have good economic efficiency. The average static and dynamic payback period are 2.69 and 3.15 respectively. Among public buildings, hotel and shopping mall have a higher energy saving potential and better investment returns. Some involved technologies have good cost performance, such as LED light, pump frequency conversion, air source heat pump, glass filming and free cooling. This study could provide support for relevant owners and policy-making of governments.